2021
DOI: 10.1093/femsec/fiab081
|View full text |Cite
|
Sign up to set email alerts
|

On the phenology of protists: recurrent patterns reveal seasonal variation of protistan (Rhizaria: Cercozoa and Endomyxa) communities in tree canopies

Abstract: Tree canopies are colonized by billions of highly specialized microorganisms that are well adapted to the highly variable microclimatic conditions, caused by diurnal fluctuations and seasonal changes. In this study we investigated seasonality patterns of protists in the tree canopies of a temperate floodplain forest via high-throughput sequencing with group-specific primers for the phyla Cercozoa and Endomyxa. We observed consistent seasonality, and identified divergent spring and autumn taxa. Tree crowns were… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 72 publications
1
3
0
Order By: Relevance
“…The responses of these communities to pathogen invasion have been extensively studied in various agricultural crops (Berendsen et al, 2018;Carrión et al, 2019;Gao et al, 2021;Kwak et al, 2018;Liu et al, 2020). Our component that is highly sensitive to fertilization (Guo et al, 2021;Zhao et al, 2019), aridity (Chen et al, 2022) and seasonal variation (Walden et al, 2021). Expanding upon these observations, our findings indicate that disease resulting from pathogen invasion can markedly alter soil-and plant-associated protistan communities.…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…The responses of these communities to pathogen invasion have been extensively studied in various agricultural crops (Berendsen et al, 2018;Carrión et al, 2019;Gao et al, 2021;Kwak et al, 2018;Liu et al, 2020). Our component that is highly sensitive to fertilization (Guo et al, 2021;Zhao et al, 2019), aridity (Chen et al, 2022) and seasonal variation (Walden et al, 2021). Expanding upon these observations, our findings indicate that disease resulting from pathogen invasion can markedly alter soil-and plant-associated protistan communities.…”
Section: Discussionsupporting
confidence: 55%
“…Protists are important components of soil and plant microbiomes, and their communities are influenced by factors such as plant compartments, sampling sites and plant health. Previous studies have shown that protists constitute a significant microbial component that is highly sensitive to fertilization (Guo et al., 2021; Zhao et al., 2019), aridity (Chen et al., 2022) and seasonal variation (Walden et al., 2021). Expanding upon these observations, our findings indicate that disease resulting from pathogen invasion can markedly alter soil‐ and plant‐associated protistan communities.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has shown a similar pattern for bacteria and protists where seasonal dynamics can lead to community homogenization over time [ 51 54 ]. Bacteria in the phyllosphere have clear seasonal patterns dependent on priority effects whereby the success of one early strain influences the outcome of the entire community [ 51 , 55 ].…”
Section: Discussionmentioning
confidence: 76%
“…Although little is known about microbial transmission and succession on plant surfaces, any transmission event may cause a change in microbial flora, depending on the type and quantity of new arrivals. Dispersal by pollinators has been shown for bacteria and fungi (Keller et al, 2021; Rebolleda Gómez & Ashman, 2019; Vannette, 2020), and even suggested for low amount protists that may act as bacterial predators (Walden et al, 2021). Furthermore, the diversity of arthropods potentially interacting with plants has been shown to affect bacterial composition and diversity on flowers and leaves (Junker, Eisenhauer, et al, 2021).…”
Section: Discussionmentioning
confidence: 99%